Inovasi dan Difusi Sistem Pendidikan Nasional: Studi Kasus Implementasi Kurikulum Nasional - Raikhan Raikhan (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The concept of this paper is to know about the process of innovation and diffusion in the application of the National Curriculum or Curriculum on 2013. Problems related to K13 have been decided from the start that have had a profound impact on National education. This is where many international writers analyze the existing process of innovation and diffusion through Rogers' toeri about the diffusion of innovation. In this case it was found that there were four factors of weakness in the diffusion process: The First: national policy but not based on proportional academic texts, the thematic approach conceptualized did not reflect integrative or interdisciplinary thematic philosophy but was multidisciplinary, so it seemed forced. And on the other hand, the interdisciplinary approach paradigm is still not many practitioners who are able to implement in the learning process. Second; Communication Aspect; the diversity of Indonesia in one hand brings grace, but on the other hand this difference is not always able to be met by policy makers in this case the government, so that in the process of communication innovation K-13 many experience difficulties due to the many differences. Third: Time, Not more than two and a half years began to be used as a policy and finally dismissed while, K-13 Innovation can be considered very fantastic. Seeing how fast the K-13 is, which can be said to be instant, how much it is difficult to say that it has succeeded in implementing the K-13 will succeed. Fourth: Social system, the inevitability that Indonesian education personnel are still weak even though the need for a learning process that focuses on competency in the era of competition is one of the right solutions by reducing the burden of teaching material and emphasizing potential exploration and all characteristics of K-13 However, the communication process and time are so fast, it is not wrong if many say that this K-13 policy is too hasty and seems forced.